Positive association of serum IgG4 levels with modified marsh classification system in children with gluten enteropathy: a single centre experience - Grotra, Rohan; Vijay, Priti; Gupta, Raj Kumar; Malhotra, Bharti (International Journal of Contemporary Pediatrics, 2024)
Background: Celiac disease or gluten enteropathy is an immune-mediated systemic disorder elicited by gluten and related prolamines in genetically susceptible individuals and is characterized by the presence of gluten enteropathy, celiac disease-specific antibodies, HLA-DQ2/DQ8 haplotypes. IgG4-related diseases is an increasingly recognized immune-mediated condition in autoimmune disorders such as primary sclerosing cholangitis, autoimmune hepatitis, and autoimmune thyroiditis, characterized by tissue fibrosclerosis and infiltration by IgG4-positive plasma cells and increased serum IgG4 concentrations. Methods: A total of 33 children with newly diagnosed celiac disease and 31 control subjects were included in this study. All suspected celiac disease children underwent duodenal biopsy and were diagnosed based on Marsh grading. Serum IgG4 level estimations were performed using an enzyme-linked immune sorbet assay method with a cut-off of 135 mg/dl for diagnosis. Results: A significant positive association between serum IgG4 levels and Marsh classification was found, the higher the levels of IgG4 in serum, the higher the grade on Marsh staging. Mean serum IgG4 levels in Marsh 3a was 126.32 mg/dl, in 3b was 171.35 mg/dl and in 3c was 209.24 mg/dl (p value=0.004) Conclusions: With increasing serum IgG4 levels, increased severity of damage was seen on biopsy specimens based on higher Marsh grade. To the best of found knowledge, this is the first study to establish the relation between IgG4 and mucosal damage in children with celiac disease.